La expedición de los decretos ejecutivos sin un control constitucional genera la violación al principio jerárquico normativo, con la consecuente vulneración a los derechos fundamentales de los ciudadanos - Carrión Espinosa, Ximena Beatriz (2015)
This study developed the theme is presented and an overview of the legal development of the Ecuadorian Civil Service throughout history, especially focused on Executive Orders issued by the Executive Branch through its supreme representative (President of the Republic ), and its incidence or social influence to cause serious negative social impacts and consequences that have affected the Ecuadorian legal system. Being a transcendental subject, it is important to note that the hierarchy is the first stop of application, the supreme law of direct application Constitution over any other, then we have the law, followed by the regulation; so it is illogical to think that a regulation or executive order can change the rules of law and even more that they are applied to change, contradict or violate the rights established by law. After thorough research and search for important aspects obtained from different literature sources, was found to have been and still are a number of cases in which individual rights are violated and collective, with bad government policies created calls towards improving the welfare of all individuals in society, and that in fact all they have is brought increasing insecurity in the Ecuadorian legal system. Situations that reveal and misinterpretation of situations or problems generated in a society, coupled with abuse of authority, the concentration of wealth in a small group among other factors have resulted in the issuance of decrees no real legal grounds to resolve such effectively the problems that occur today, with the misapplication of a true administration of justice, the systematic involvement generators of the fundamental rights of citizens. It is essential, then, through the development of this research process, presenting a viable solution to establish a reform that allowed any constitutional control to limit the power that the executive branch has to issue decrees that violate the normative hierarchical principle in their application and in turn causing the violation of fundamental rights of citizens, so that they are protected and covered the guarantees established in the Constitution and the law.